HIV-1 subtype diversity and phylogenetic insight into non-B subtype transmission in Slovenia, 1989-2013 - Mlakar, Jana (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2023)
Introduction: Disease progression, drug resistance mutations, and treatment strategies may vary by HIV-1 subtype. This study determined HIV-1 subtypes circulating in Slovenia, a Central European country with an HIV-1 epidemic driven by men who have sex with men, focusing on molecular epidemiology of non-B subtypes. Methods: A total of 367 HIV-1 sequences were included. Subtype was assigned by employing eight different HIV subtyping tools coupled with maximum likelihood phylogenetic analyses. Results: The subtyping tools COMET, jpHMM, and REGA 3.0 exhibited the best performance on the dataset studied. Phylogenetic analyses showed a 14.7% prevalence of non-B subtypes, with subtype A detected most frequently (4.9%), followed by CRF02_AG (2.4%), subtype C (1.1%), subtypes D, G, and CRF01_AE (0.8% each), and subtypes F and CRF22_01A1 (0.3% each). A subtype could not be assigned to 12 sequences (3.3%), indicating potential unique recombinant forms. Non-B subtypes were significantly associated with a heterosexual route of transmission and infection acquired in Eastern Europe, Africa, or Asia. Conclusions: In a country where subtype B is predominant, non-B subtypes were observed in one out of seven patients, a nonnegligible proportion, which underlines the importance of systematic surveillance of HIV subtype diversity and the corresponding molecular epidemiology.
Keywords: Central Europe; filogenija; HIV-1; molecular epidemiology; molekularna epidemiologija; ne-B podtip; non-B subtype; phylogeny; podtipiziranje; srednja Evropa; subtyping